Improving Equitable Access to Graduate Education by Reducing Barriers to Minoritized Student Success - David M. Rehfeld; Rachel Renbarger; Tracey Sulak; Abby Kugler; Payton DeMeyer (MDPI AG, 2024)
Structural inequities in graduate education perpetuate inequity for students with historically minoritized identities. This paper reviews previous reports of inequities faced by students with minoritized identities and suggests a path forward for improving equitable access to doctoral study. Specifically, this paper suggests investing in the scholarship of teaching and learning while using Gardner's model of doctoral student development to provide targeted support at different levels of operation: the institution, the department, and the individual. Evidence for suggested supports is also provided and a call for further research on the effects of such programs for recruitment, retention, and graduation of minoritized students is made.